(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose. The article examines the motifs of memory and forgetting as fundamental categories that shape the development of tragic discourse in twentieth-century literature. The analysis is grounded in Mikhail Bakhtin’s concept of cultural memory and its structuring potential, as well as in selected theoretical insights of Paul Ricœur, Maurice Blanchot, and Pierre Nora, which illuminate the mechanisms of literary representation of the past. Memory is approached as a poetic principle that organizes narrative structure, establishes chronotopic coherence, and sustains the motif-based configuration of the text. Forgetting, conversely, is interpreted as an aesthetically conditioned strategy that produces narrative ruptures, semantic shifts, and zones of indeterminacy, thereby contributing to the emergence of the tragic dominant. The practical section focuses on a comparative reading of Kazuo Ishiguro’s An Artist of the Floating World and Abdizhamil Nurpeisov The Last Duty. These novels demonstrate distinct ways of engaging with a disappearing past: Ishiguro foregrounds fragmented, variable, and often unstable recollections, while Nurpeisov constructs a persistent network of motifs that preserves the coherence of a lost cultural and spatial world. In both texts, the dynamic interplay between memory and forgetting generates internal narrative tension and operates as a central mechanism in producing tragic meaning. The study is exploratory in nature and systematizes major theoretical approaches to these motifs, offering a methodological framework for further investigations into the poetics of the tragic within twentieth-century prose.